2017
DOI: 10.1021/acsmedchemlett.7b00192
|View full text |Cite|
|
Sign up to set email alerts
|

Apratoxin S10, a Dual Inhibitor of Angiogenesis and Cancer Cell Growth To Treat Highly Vascularized Tumors

Abstract: Renal, hepatocellular, and neuroendocrine carcinomas are known as highly vascularized tumors. Although vascular endothelial growth factor A (VEGF-A)-targeted therapies have shown efficacy in the treatment of these cancers, drug resistance is a major concern and might be mediated by interleukin 6 (IL-6). Furthermore, upon antiangiogenic drug exposure, tumor cells may adapt to survive in a vascular-independent manner. Apratoxins are potent marine-derived cytotoxic in vivo-active agents, preventing cotranslationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…Apratoxins were previously reported to exert its function by inhibiting protein co-translational translocation at the level of Sec61 translocon, leading to downregulation of various receptor tyrosine kinases and growth factors. 13,14,[16][17][18]36 Consistent with these observations [20], receptor tyrosine kinase VEGFR2 and VEGFR3 expressions were significantly inhibited in Apratoxin S4-treated HRECs. Similarly, receptor tyrosine kinase PDGFR-b level in HRPCs was also suppressed by Apratoxin S4.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Apratoxins were previously reported to exert its function by inhibiting protein co-translational translocation at the level of Sec61 translocon, leading to downregulation of various receptor tyrosine kinases and growth factors. 13,14,[16][17][18]36 Consistent with these observations [20], receptor tyrosine kinase VEGFR2 and VEGFR3 expressions were significantly inhibited in Apratoxin S4-treated HRECs. Similarly, receptor tyrosine kinase PDGFR-b level in HRPCs was also suppressed by Apratoxin S4.…”
Section: Discussionsupporting
confidence: 74%
“…Natural and synthetic Apratoxins are potent antitumor and antiangiogenic macrocyclic depsipeptides derived from marine cyanobacteria. [16][17][18]35,36 It was reported that Apratoxins exert their function through inhibiting co-translational translocation of secreted or membrane bound proteins, 13 which may offer an alternative way to control the activation of angiogenic pathways.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations